Penggunaan Aplikasi Laiba Sebagai Media Edukasi Mengenai Kewajiban Menuntut Ilmu Dalam Islam - Rika Yulia; Nisa Aulia; Annisa Putri Heryani; Ani Nur Aini (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
Technology plays an important role in human life, one of which is in the field of education. The rapid development of technology, especially since the pandemic, has encouraged the emergence of various media or applications that are useful in student learning. Seeking knowledge means effort or endeavor in learning a science, both worldly knowledge or hereafter science. We have observed several 2nd grade students at SDN Panyingkiran II, Kab. Sumedang. This research was conducted using a design and development research model. Where the results of this study indicate the design and product in the form of an Android-based application and named the Laiba Application. By making this application, it is expected that students can understand the meaning of the obligation to study in Islam. Another goal is to make it easier for elementary school students to access or study learning materials regarding Hadith, the obligation to seek knowledge, even if they are at home or in other places. Based on the observations that have been made, by showing the application that we have made and asking some questions, we can draw some conclusions about the application that we have made, namely (1) All students agree that the application is interesting. Because in addition to reading material with cute icons, this Laiba application also contains funny animated videos and practice questions that can be filled out repeatedly and the use of the application is easy to use, even the use of space or memory on the cellphone does not take up much space. large, (2) Some of the children listened with focus. (3) Some children understand and can re-explain the material discussed and given.